STUDENTS’ EVALUATION OF TEACHERS: IS IT AGAINST THE VIETNAMESE CULTURAL NORM? - Tuyet, Tran Thi (VNU Journal of Foreign Studies; Vol 34 No 6, 2018)
Students’ evaluation of teachers has become a popular activity in professional development and teaching evaluation in the higher education systems worldwide. In Vietnam, this activity has been carried out in universities in the last 10 years, however, the implementation of this activity faces many difficulties as it is considered against the cultural norm in a Confucian Heritage Culture where students are not often allowed to comment on their teachers’ teaching. This article, based on the findings of a quantitative research study, reports the change in attitude of teachers in a university towards this against-the-cultural-norm-movement. The findings indicate that the negative attitude toward this activity has virtually disappeared when this activity was redesigned taking into account teachers’ comments and needs, local university characteristics and cultural thinking. It is clear from the findings that if the above factors are taken into account, student’s evaluation of teachers is not considered to be against the cultural norm of respecting teachers in Vietnam.